A conceptual framework for culturally appropriate advocacy with racialised groups - Salla, Anthony; Newbigging, Karen; Joseph, Doreen; Eneje, Emachi (Frontiers in Psychiatry, 2023)
Independent mental health advocacy was introduced in England to protect and promote the rights of people detained under mental health legislation. However, shortcomings in access and delivery to racialised people, raising concerns about equity, were identified by a review of the Mental Health Act. The development of culturally appropriate advocacy was recommended. While the term culturally appropriate may be taken for granted it is poorly defined and limited efforts have conceptualized it in relation to advocacy. Ideally, advocacy operates as a liberatory practice to challenge epistemic injustice, which people experiencing poor mental health are at acute risk of. This is amplified for people from racialised communities through systemic racism. This paper argues that advocacy and culturally appropriate practices are especially relevant to racialised people. It clarifies the importance of culture, race and racism to the role of advocacy, and understanding advocacy through the conceptual lens of epistemic injustice. A central aim of the paper is to draw on and appraise cultural competency models to develop a conceptual framing of cultural appropriate advocacy to promote epistemic justice.